Utilization of Chicken Egg Shells as Adsorbents for Indigosol Blue Dyes with Variations of Activators - Rustiana, Tuti; Aprilani, Mira; Safitri, Bella; Wanti, Luthfiah Sekar (Jurnal Pijar Mipa, 2025)
The textile industry still has serious problems in managing waste disposal that causes environmental pollution, including the batik factory industry. Many studies have been conducted to overcome ecological damage by reducing the levels of dyes contained in textile industry waste. Apart from textile industry waste, household waste, especially egg shells, is very high. One alternative method for processing batik factory liquid waste is by adsorption using biosorbent, which is considered cheaper and easier to obtain. An example of a biosorbent is an eggshell. This study includes the characterization of eggshells activated by NaOH and HCl for Indigosol Blue adsorption, morphological analysis of eggshells with SEM and EDS, wavelength determination, calibration curve, and adsorption capacity. The morphology of the eggshell shows a porous surface with high levels of calcium, oxygen, and carbon, indicating that the main compound forming the eggshell is CaCO3. The determination of maximum wavelength and adsorption capacity is done using the UV-Vis spectrophotometry method. The maximum wavelength is 530 nanometers, and an R2 value of 0.9596 was obtained from the regression curve equation. Characterization according to SNI eggshell before activation water content: 0.34%, ash content: 0.25%, iodine absorption: 326.552mg/gram and after activation with NaOH water content is 1.34%, ash content: 0.39%, iodine absorption: 403.015mg/gram. The optimal concentration of processed egg shells for indigosol blue adsorbent is 2% egg shells, the largest in this study as an adsorbent. It turns out that adsorption is still ongoing. The optimum type of activator for Indigosol Blue absorption is 100Mesh dry eggshell powder from NaOH activation.